GENDER STUDIES IN THE QURAN: INTERPRETATIONS OF WOMEN'S ROLES AND RIGHTS - Achmad Zahruddin (CV. Adiba Aisha Amira, 2024)
In the context of the Quran, the term gender refers to the concept of separation of roles, characteristics, and responsibilities between men and women based on the interpretation of sacred verses. The Quran addresses the concept of gender not only as a biological difference, but also as a complex social and spiritual construct. It emphasises the equal spiritual dignity of men and women before God, while recognising differences in function in some aspects of social and family life. The understanding of gender in the Quran has been the subject of diverse interpretations throughout Islamic history, with contemporary interpretations tending to emphasise the principles of equality and justice, while still appreciating the distinctiveness of each sex within the framework of Islamic ethics and spirituality. The study in this research uses the literature study method. The results found that; Firstly, the Quran fundamentally affirms the equality of men and women in terms of spiritual and human values. Although some traditional interpretations tend to limit the role of women, contextual and linguistic analyses of Quranic verses show that the holy book supports women's active participation in various aspects of life, including social, economic and political. Secondly, the Quran grants women a variety of progressive rights for the time, including the right to education, employment, property ownership, and marital justice. However, the implementation of these rights is often hindered by interpretations influenced by patriarchal culture and specific socio-historical contexts.